Optimization of Conditions for High Cell Density Cultivation of Bacillus Subtilis - Lew, Kok Cheong (2006)
The objectives of this study are (i) To investigate the effect of using different types of carbon source and their concentration on the growth of B. subtilis, (ii) To optimize the pH condition for improvement of growth of B. subtilis through the different pH control strategies and (iii) To develop high cell density cultivation methods for B. subtilis based on exponential fed-batch fermentation. Preliminary, the effects of different carbon sources such as glucose, sucrose, starch hydrolysate and sago starch on growth performance of B. subtilis was investigated using batch fermentation technique. Subsequently, the effects of different initial glucose concentrations, which is the preferred carbon source for growth of this bacterium, was studied in batch fermentation. The experiment was designed to find the repression effect of glucose on growth of B. subtilis. The culture pH condition for growth of B. subtilis was also optimized using different pH control strategies. The exponential fed-batch fermentation aimed at production of high cell density of B. subtilis was developed using kinetic parameter values and information generated from the preliminary batch fermentation data. Fed-batch fermentations were carried out at different required specific growth rates and their effects on final cell concentration attained, yield and productivity were analyzed. The performance of fed-batch fermentation with controlled glucose concentration at certain level in the culture for improvement of B. subtilis cultivation was also investigated.